Fatigue resistance of bovine teeth restored with resin-bonded fiber posts: Effect of post surface conditioning - Zamboni, Sandra C. [UNESP]; Baldissara, Paolo; Pelogia, Fernanda [UNESP]; Bottino, Marco Antonio [UNESP]; Scotti, Roberto; Valandro, Luiz Felipe (My University, 2008)
This study evaluated the effect of post surface conditioning on the fatigue resistance of bovine teeth restored with resin-bonded fiber-reinforced composite (FRC). Root canals of 20 single-rooted bovine teeth (16 mm long) were prepared to 12 mm using a preparation drill of a double-tapered fiber post system. Using acrylic resin, each specimen was embedded (up to 3.0 mm from the cervical part of the specimen) in a PVC cylinder and allocated into one of two groups (n = 10) based on the post surface conditioning method: acid etching plus silanization or tribochemical silica coating (30 μm SiOx + silanization). The root canal dentin was etched (H2PO3 for 30 seconds), rinsed, and dried. A multi-step adhesive system was applied to the root dentin and the fiber posts were cemented with resin cement. The specimens were submitted to one million fatigue cycles. After fatigue testing, a score was given based on the number of fatigue cycles until fracture. All of the specimens were resistant to fatigue. No fracture of the root or the post and no loss of retention of the post were observed. The methodology and the results of this study indicate that tribochemical silica coating and acid etching performed equally well when dynamic mechanical loading was used.
Keywords: acrylic acid resin; glass; glass fiber; resin; resin cement; tooth cement; animal; cattle; cementation; chemistry; dental acid etching; dental bonding; dental care; dental surgery; dentin; drug effect; endodontics; instrumentation; materials testing; methodology; surface property; tooth crown; tooth prosthesis; Acid Etching, Dental; Acrylic Resins; Animals; Cattle; Cementation; Composite Resins; Dental Bonding; Dental Cements; Dental Prosthesis Retention; Dental Restoration Failure; Dental Stress Analysis; Dentin; Glass; Materials Testing; Post and Core Technique; Resin Cements; Root Canal Preparation; Surface Properties